Posterior cruciate ligament resection under minimum medial collateral ligament release changes tibial internal rotation, joint center gap, and varus ligament balance on joint distraction force at flexion in total knee arthroplasty. (February 2023) - Motoyama, Mitsuru; Takemoto, Shozui; Kato, Tomohiro; Joji, Shigeo; Yamamoto, Risako; Deie, Masataka; Adachi, Nobuo
Abstract: Background: The purpose of this study was to assess the effect of posterior cruciate ligament resection under minimum medial collateral ligament release on the joint center gap, varus ligament balance, and the rotational change of the femur and tibia. Methods: This study included 75 knees with varus osteoarthritis that underwent total knee arthroplasty. After minimum medial collateral ligament releases and bone resection of the distal femur and proximal tibia, the joint center gap and varus ligament balance were measured before and after posterior cruciate ligament resection using a digital tensor with a joint distraction force of 89, 133, 178 N. The rotational changes under a distraction force of 200 N were captured using a navigation system. Findings: The joint center gap and varus ligament balance at 90° and 120° of flexion significantly increased after posterior cruciate ligament resection with distraction forces of 89 N (90°: 0.4 mm / 0.9° and 120°: 0.5 mm / 0.8°), 133 N (90°: 0.9 mm / 1.3° and 120°: 0.9 mm / 1.1°), 178 N (90°: 1.5 mm / 1.9° and 120°: 1.5 mm / 1.5°). Tibial internal rotation significantly increased after posterior cruciate ligament resection at 90° (1.9°) and 120° (2.2°). Interpretation: Joint distraction forces after posterior cruciate ligament resection increased the tibial internal rotation, joint center gap, and varus ligament balance at flexion. These findings indicate that posterior cruciate ligament resection should increase the lateral gap more than the medial gap due to tibial internal rotation at flexion. (245 words). Highlights: Posterior cruciate ligament resection raises flexion gap by an average of 1.5 mm with a force of 178 N. Posterior cruciate ligament resection increases the tibial internal rotation at flexion. Posterior cruciate ligament resection increases the lateral gap more than the medial gap at flexion.